ORGANIZING INDEPENDENT EDUCATION OF STUDENTS IN THE CREDIT-MODULE SYSTEM - Ilhom Dostnazarovich Ganiyev (Journal Park Publishing, 2022)
The credit-module system has brought to the system of higher education of our country a unit of measurement that is more perfect and effective than the current education, modern, but understandable to everyone. The article talks about the organization and methodology of students' independent work in the credit-module system, as well as the audience and independent hours in the credit-module system, as well as the quality of students' independent work.
Keywords: ECTS credit module, methodology, portfolio, pedagogue, student, ability, independent education, TMI.